An online dictionary of the professional language of Polish press journalists. The concept of domain-specific wordnet-like thesaurus – preliminary comments - Jarosz, Beata (Papers in Linguistics, 2024)
The article presents an initial concept of the domain-specific wordnet-like thesaurus containing special nomenclature used by Polish press journalists in intra-group communication in the course of performing professional tasks. Of approximately 2,600 specialized lexical units used from the 18th century to the present day, only a fraction have so far been included in dictionaries, which justifies the need to build an e-dictionary. Based on test work done by the author at the CLARIN-PL center (Poland), and with regard to the methodology of creating general wordnets, including the concept of the Polish general wordnet (Słowosieć), the content of the journalistic thesaurus and the scope of information included in headword entries were preliminarily specified. Additionally, the author defined a preliminary catalogue of semantic domains and semantic relations by which specific lexical units will be ordered. Moreover, the method of connecting resources with the PlWordNet was proposed. The article initiates discussion on the essence and methodology of building domain-specific wordnets, the construction of which is experimental due to the lack of this kind of Polish projects and only a few global ones (e.g. ArchiWordNet, Jur-WordNet).